Cervical Stump Fibroidpost Supra-cervical Hysterectomy - Sherman David Mathew; Betsy Abraham (Faculty of Medicine Universitas Padjadjaran, 2018)
Objective: To describe of a rare case of cervical stump fibroid presenting as a late complication of supra-cervical hysterectomy.Methods: A 68-year old-female with a history of lower abdominal pain and distention for six months with increasing intensity was referred from a local clinic to the department of radio-diagnosis for evaluation. She had a history of subtotal hysterectomy previously. On ultrasonography and computerized tomography imaging studies, a large adnexal lesion was noted suggesting the possibility of a cervical stump leiomyoma. The patient underwent an elective surgery and the diagnosis was confirmed in the context of histological findings.Results: Patient was operated for the radiologically diagnosed large cervical stump leiomyoma which was laterhistologically confirmed with an uneventful recovery.Conclusions: Imaging investigations like computerized tomography and magnetic resonance imaging are valuable in the diagnosis of rare adnexal masses from cervical stump arising as late delayed complications of supra-cervical hysterectomy. Keywords: Cervical stump leiomyoma, computerized tomography, magnetic resonance imaging, supra-cervical hysterectomy DOI: 10.15850/ijihs.v6n2.1257